2018
DOI: 10.14260/jemds/2018/42
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Metabolic Disorders in Vertigo

Abstract: BACKGROUND Vertigo is a common medical condition, affecting around 1.8% of young adults to more than 30% in the elderly. Metabolic disorders commonly related to labyrinthine dysfunctions are glucose metabolism changes (diabetes, reactive hypoglycaemia and hyperinsulinaemia), thyroid hormones and lipid metabolism disorders. The objective of this study is to compare the prevalence and association of metabolic disorders in vertigo cases to control under study. MATERIALS AND METHODS A case controlled study was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Bepari et al 20 , when evaluating the hemograms of a group of diabetic patients, identified high values of thyroid-stimulating hormone (T3, T4 and TG), besides the increase in low-density lipids (LDL). The increase in serum cholesterol is one of the risk factors for the development of atherosclerosis, which also has a role in the vestibulocochlear vessels, especially in individuals over 40 years old.…”
Section: Iibmentioning
confidence: 99%
See 2 more Smart Citations
“…Bepari et al 20 , when evaluating the hemograms of a group of diabetic patients, identified high values of thyroid-stimulating hormone (T3, T4 and TG), besides the increase in low-density lipids (LDL). The increase in serum cholesterol is one of the risk factors for the development of atherosclerosis, which also has a role in the vestibulocochlear vessels, especially in individuals over 40 years old.…”
Section: Iibmentioning
confidence: 99%
“…The increase in serum cholesterol is one of the risk factors for the development of atherosclerosis, which also has a role in the vestibulocochlear vessels, especially in individuals over 40 years old. Hence, the importance of multidisciplinary clinical follow-up is highlighted, including hormonal and dietary therapy 20 .…”
Section: Iibmentioning
confidence: 99%
See 1 more Smart Citation